Outbreak of rabbit hemorrhagic disease virus 2 in the southwestern United States: first detections in southern California - Asin, Javier (J Vet Diagn Invest, 2021)
An outbreak of rabbit hemorrhagic disease virus 2 (RHDV2)-associated disease occurred in the southwestern United States following its first detection in New Mexico in March 2020. The disease spread throughout several states and was diagnosed for the first time in California on May 11, 2020, in a black-tailed jackrabbit (Lepus californicus). The following day, the California Department of Food and Agriculture (CDFA) issued an order banning the entrance into California of several lagomorph species and their products from any state in which the disease had been detected in the last 12 mo. RHDV2 is a threat to wild lagomorph species in California, including the endangered riparian brush rabbit (Sylvilagus bachmani riparius). Therefore, the California Department of Fish and Wildlife (CDFW) started tracking any mortality event in wild lagomorph populations. As of August 9, 2020, RHDV2 had been detected in wild and domestic lagomorphs of several counties in southern California that were submitted to the California Animal Health and Food Safety laboratory system by the CDFA or the CDFW. These positive cases included 2 additional black-tailed jackrabbits and 3 desert cottontail rabbits (Sylvilagus audubonii). In addition, the infection spilled over to domestic populations, whereby it was confirmed on July 10, 2020, in a domestic rabbit (Oryctolagus cuniculus).